Strategi Pengembangan Wisata Religi Pura Giri Sutra Mandala - Iis Purniawati; Neli Aida; Arivina Ratih; Asih Murwiati (CV. Multi Kreasi Media, 2022)
Giri Sutra Mandala Temple is a religious tourism object that has the potential to be developed. The tourism development of the Giri Sutra Mandala Temple is expected to increase the economy of the local community and regional income in Pringsewu Regency. This study aims to determine the right strategy in the tourism development of Pura Giri Sutra Mandala by using SWOT analysis. Researchers will identify internal factors and external factors that are owned by Pura Giri Sutra Mandala by means of observation and interviews with resource persons. Then input into the form of a questionnaire that will be used to analyze the weights and ratings on the IFAS Matrix and the EFAS Matrix. The next step is to create a SWOT Matrix. The SWOT Matrix is ​​used to formulate strategies by combining existing strengths, weaknesses, threats, and opportunities. The final step is making a decision using the SWOT Quadrant. The results of this study indicate that the tourism development strategy of the Giri Sutra Mandala Temple is to maximize the potential of the temple such as optimizing the temple building and the natural beauty around the temple, increasing various religious activities, optimizing facilities and accessibility, and adding members pecalang and BHABINKAMTIBMAS.